Interbank network as a channel of credit contagion in banks: Is moral hazard transferable? - Željko Jović; Milena Lutovac aković (Journal of Central Banking Theory and Practice, 2022)
The objective of this research is to examine the inter-bank network of clients as a channel for credit risk transmission by groups of banks in Serbia characterized by different levels of credit risk (clusters). Two of the four observed groups of banks have experienced increase in NPLs through the channel of contagion spread in the interbank network. The spread of the infection through the banking network is a consequence of the impact of the economic connection among clients. The third group of banks (banks with high levels of credit risk) takes over the effects of systemic factors and transfers their influence to the second and the first group (banks with average and below-average credit risk level) through the banking network channel. There were different models of bank behaviour, from a group of banks that fully aligned their risk taking with risk capacity to a group of banks that exhibited an excessive risk propensity far beyond their own risk-taking capacity. There is also the confirmation that moral hazard was an important determinant of credit risk and an additional impulse to spread credit contagion.
Keywords: G21; G28; G32; D82; 330; Credit Contagion; Interbank Network; Economic Con-nection; Moral Hazard; NPL